2012
DOI: 10.1302/0301-620x.94b8.28135
|View full text |Cite
|
Sign up to set email alerts
|

Metal hypersensitivity testing in patients undergoing joint replacement

Abstract: We report a systematic review and meta-analysis of the peer-reviewed literature focusing on metal sensitivity testing in patients undergoing total joint replacement (TJR). Our purpose was to assess the risk of developing metal hypersensitivity post-operatively and its relationship with outcome and to investigate the advantages of performing hypersensitivity testing. We undertook a comprehensive search of the citations quoted in PubMed and EMBASE: 22 articles (comprising 3634 patients) met the inclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
138
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 152 publications
(147 citation statements)
references
References 49 publications
0
138
0
9
Order By: Relevance
“…This approach is similar to that suggested by Granchi et al [25], who performed a comprehensive systematic review on metal allergy and total joint replacement in 2012. Thyssen et al [197] took it a step further and recommended that clinicians refrain from carrying out routine patch testing prior to surgery, unless the patient reports having a history of clinical metal intolerance of a magnitude sufficient to cause concern to the patient or to the doctor.…”
Section: Is There a Need For Allergy Testing Before Implantation?mentioning
confidence: 78%
See 3 more Smart Citations
“…This approach is similar to that suggested by Granchi et al [25], who performed a comprehensive systematic review on metal allergy and total joint replacement in 2012. Thyssen et al [197] took it a step further and recommended that clinicians refrain from carrying out routine patch testing prior to surgery, unless the patient reports having a history of clinical metal intolerance of a magnitude sufficient to cause concern to the patient or to the doctor.…”
Section: Is There a Need For Allergy Testing Before Implantation?mentioning
confidence: 78%
“…In 2012, the same group performed a systematic review and meta-analysis of peer-reviewed literature that focused on metal sensitivity testing in patients undergoing total joint replacement. They found that the probability of developing a metal allergy was higher after surgery (OR, 1.52; 95%CI, 1.06-2.31) and that the risk was even higher when failed implants were compared with stable total joint replacements (OR, 2.76; 95%CI, 1.14-6.70) [25]. A few recent prospective studies have also suggested an increase in cases of metal allergy following THA, even in patients with well-functioning prostheses [26][27][28].…”
Section: The Rising Potential Impact Of Metal Hypersensitivitymentioning
confidence: 99%
See 2 more Smart Citations
“…The probability of developing a metal allergy seems to be higher post-operatively and the risk further increased when failed implants were compared with stable TJRs [8] …”
mentioning
confidence: 99%